Income Inequality and Labor Share in U.S.A and Canada - Islam, Sadequl; Safavi, Mohammad (Archives of Business Research, 2019)
In recent years, in many countries, income inequality has increased while the labour share of income has declined. Using the Standardized World Income Inequality Database, we examine if income inequality, measured by the GINI Index, is related to the labor share of income in the U.S. and Canada. The paper uses time series regressions for the 1981–2011 period. Although apparently correlated, regression results confirm that declines in the labor income share have not had significant effects on income inequality.